2022
DOI: 10.1186/s12909-022-03774-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and perceptions of medical students towards mental health in a university in Uganda

Abstract: Background The prevalence of mental illness among medical students is high. A gap remains on what knowledge should be given to improve the attitudes and perceptions towards mental health. Despite the vast body of literature globally, no study has been conducted in Uganda to assess the levels of knowledge, attitude, and perception among medical students in Uganda. Objective To determine the level of knowledge, attitude, and perception and their asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…One of the significant risk factors associated with poor knowledge of mental illness was not having studied psychology or psychiatry formally. In line with previous studies, those who received formal education about psychiatry, such as medical students, tend to have higher knowledge of mental health [8,15]. Our result emphasizes the need to improve students' mental health literacy and mental health education in university curriculums.…”
Section: Discussionsupporting
confidence: 89%
“…One of the significant risk factors associated with poor knowledge of mental illness was not having studied psychology or psychiatry formally. In line with previous studies, those who received formal education about psychiatry, such as medical students, tend to have higher knowledge of mental health [8,15]. Our result emphasizes the need to improve students' mental health literacy and mental health education in university curriculums.…”
Section: Discussionsupporting
confidence: 89%
“…Among the study respondents, 379(93.3%) of the respondents need not have mental health services and only 27(6.7%) received mental health services. This is corroborated by the findings of Kihumuro RB et al, who found that the majority 86.73% not receive mental health services while only 13.27% need to have such services [20]. Regarding General Anxiety Disorder(GAD) , of respondents 191(47.1%) had no GAD, 166(40.9%) had mild, 28(6.9%) had moderate and only 21(5.1%) had severe disorder.…”
Section: Discussionmentioning
confidence: 55%
“…Most of the studies that have been done on medical students/doctors with regard to attitude toward mental illness had a proportion of knowledge from as low as 45% to as high as 75%. [ 17 , 18 ] In our study, we have taken the estimated proportion of knowledge regarding mental health problems as 75%, with 95% confidence level, and 5% margin of error. Accordingly, the sample size was calculated [ n = (zα/2) 2 P (1 − p)/d2].…”
Section: Methodsmentioning
confidence: 99%